Determinants of Small-Scale Irrigation Use and Its Effect on Household Food Security in Dibay Tilatgin Woreda, East Gojjam zone, Ethiopia - Assefa, Natnael Yasab (International Journal of Scientific Research in Civil Engineering, 2020)
In Ethiopia, agriculture is the primary determinant of economic growth and reducing level of food insecurity. But in the country in general and study area in particular, agriculture is dominated by small-scale rain-fed production. As a result, the current yield level by rural smallholder farmers in the study area has not been able to fulfill the minimum food requirements. To this end, this research aims to identify determinants of SSI use and its effect on household food security status in Dibay Tilatgin, Amhara regional state, Ethiopia. Multistage sampling technique and Kothari formula was employed to identify the final sample respondents; accordingly the final sample size was 168 (38.7% irrigation users and 61.3% non-users). Both quantitative and qualitative data from primary and secondary sources were collected through interview schedule. Descriptive, inferential statistics and binary logistic model were used to analyze the collected data. The finding of the study revealed that sex, education, household labor size, cultivable land size, frequency of extension contact, training and credit use had significant positive influence whereas farm distance from water source  had significant negative influence on SSI use. Out of the total sample households, 72 (42.9%) were food secure and 96 (57.1%) were food insecure. The study result also reported, SSI had significant and positive influence on HFSS at 1% level. Therefore, it is important to address factors affecting SSI use includes sex, education level, household labor size, cultivable land size, farm distance from water sources, training and also priority should be given to SSI development in planning and executing of policies and programs by all stakeholders.
Keywords: Household; Food Security; Binary; Logit